Adoptive transfer of EBV-specific T cells results in sustained clinical responses in patients with locoregional nasopharyngeal carcinoma - Louis, Chrystal U (2010)
Patients with recurrent or refractory Epstein Barr virus (EBV)-positive nasopharyngeal carcinoma (NPC) continue to have poor outcomes. Our earlier Phase I dose escalation clinical study of 10 NPC patients showed that infusion of EBV-specific cytotoxic T cells (EBV-CTLs) was safe and had antitumor activity. To better define the overall response rate and discover whether disease status, EBV-antigen specificity, and/or in vivo expansion of infused EBV-CTLs predicted outcome, we treated 13 additional NPC patients with EBV-CTLs in a fixed-dose, Phase II component of the study. We assessed toxicity, efficacy, specificity and expansion of infused CTLs for all 23 recurrent/refractory NPC patients treated on this Phase I/II clinical study. At the time of CTL infusion, 8 relapsed NPC patients were in remission and 15 had active disease. No significant toxicity was observed. Of the relapsed patients treated in their second or subsequent remission, 62% (5/8) remain disease free (at 17-75 months), while 48.7% (7/15) of those with active disease had a CR/CRu (33.3%) or PR (15.4%). In contrast to locoregional disease, metastatic disease was associated with an increased risk of disease progression (HR: 3.91, p=0.015) and decreased overall survival (HR: 5.55, p=0.022). Neither the specificity of the infused CTLs for particular EBV antigens nor their measurable in vivo expansion discernibly influenced outcome. In conclusion, treatment of patients with relapsed/refractory EBV-positive NPC with EBV-CTLs is safe and can be associated with significant, long-term clinical benefit, particularly for patients with locoregional disease.